The Palgrave Handbook of Global Counterterrorism Policy
XIX, 1098 p. 5 illus.
Keywords: The Palgrave Handbook of Global Counterterrorism Policy examines a comprehensive range of counterterrorism policies, strategies, and practices across dozens of states and actors around the world. It covers the topics of terrorism and counterterrorism both thematically and by region, allowing for discussions about the underpinning dynamics of these fields, consideration of how terrorism and counterterrorism are evolving in the modern period, and in-depth analyses of individual states and non-state actors, and their approaches to countering terrorism and terrorist threats. It draws upon a multidisciplinary range of established scholars and upcoming new researchers from across multiple fields including political science and international relations, sociology, and history, examining both theory and practice in their respective chapters. This volume is an essential resource for scholars and practitioners alike.